Die signifikanten Merkmale der entdeckten Amduat-Fragmente im Grab KV 38 - Ghany, Khaled Abdel (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
In 2019 and as part of the project “Thutmose’ I Amduat-Specimen”, further research work was performed at the tomb KV 38. During last course of this exploration, I achieved to secure more small mud-plaster fragments of the Book of Amduat, of which the cliff walls of the burial chamber were decorated. These different Amduat fragments can be identified as a part of the fourth, eighth, and ninth hour of the Book of Amduat. About the ninth hour there had never been a hint or a corresponding mention of it before. Therefore, this is also a piece of new archaeological evidence. After a comparative analysis of the paleographic and iconographic features of the displayed scenes on the newly found Amduat fragments with similar scenes from the tomb KV 34, it could be proved that there is a definite development between the time of Thutmose I and his successors. Furthermore, these sections highlight the iconographic features of the Amduat version of Thutmose I – their characteristic attributes and archaic decoration style form the original basis on which all subsequent versions have been built. Thus, this version could be the earliest source of the theological underworld books of the early 18th Dynasty.